John Balckie & Co., Merchant Tailors; O.L. Gillett, Cigar Manufacturer - Sampson, Davenport, & Co. (Tufts Archival Research Center, 2005)
Page image of John Balckie & Co., Merchant Tailors; O.L. Gillett, Cigar Manufacturer from the 1870 Boston City Directory